Selection Profile of Student Training Education Center (PPLP) Taekwondo Athletes, Southeast Sulawesi Province 2021 - Bayu Thomi Rizal; Habibie Habibie; Dadi Surjadi (STKIP Muhammadiyah Kuningan, 2022)
The profile of the selection results to enter the Student Sports Training Education Center (PPLP) for the taekwondo sport of Southeast Sulawesi Province in 2021 was carried out to be a recommendation in preparing athletes who will take part in the next PPLP taekwondo selection activity in Southeast Sulawesi Province. The tests and measurements were followed by 30 male and female athletes candidates. The sampling technique in this study used a total sampling technique. The sample used in this study were 30 prospective PPLP taekwondo athletes in Southeast Sulawesi. The test instrument used refers to the PPLP selection test results from the Ministry of Youth and Sports of the Republic of Indonesia. The tests used in taekwondo include 1) anthropometry tests using the athlete's body mass index, 2) speed tests using a 30-meter run, 3) abdominal muscle strength tests using Sit-Ups, 4) power tests using the Beep Test, and 5) psychological tests using anxiety instruments before, during, and before competing. Furthermore, it is hoped that taekwondo sports coaches can develop their athletes to participate in the PPLP selection in the following year to achieve maximum results.